Endocannabinoids produced in photoreceptor cells in response to light activate Drosophila TRP channels. - Sokabe, T.; Bradshaw, H.B.; Tominaga, M.; Leishman, E.; Chandel, A.; Montell, C. (Science signaling, 2022)
Drosophila phototransduction is a model for signaling cascades that culminate in the activation of transient receptor potential (TRP) cation channels. TRP and TRPL are the canonical TRP (TRPC) channels that are regulated by light stimulation of rhodopsin and engagement of G?q and phospholipase C? (PLC). Lipid metabolite(s) generated downstream of PLC are essential for the activation of the TRPC channels in photoreceptor cells. We sought to identify the key lipids produced subsequent to PLC stimulation that contribute to channel activation. Here, using genetics, lipid analysis, and Ca2+ imaging, we found that light increased the amount of an abundant endocannabinoid, 2-linoleoyl glycerol (2-LG), in vivo. The increase in 2-LG amounts depended on the PLC and diacylglycerol lipase encoded by norpA and inaE, respectively. This endocannabinoid facilitated TRPC-dependent Ca2+ influx in a heterologous expression system and in dissociated ommatidia from compound eyes. Moreover, 2-LG and mechanical stimulation cooperatively activated TRPC channels in ommatidia. We propose that 2-LG is a physiologically relevant endocannabinoid that activates TRPC channels in photoreceptor cells.